PENGARUH KESADARAN WAJIB PAJAK DAN KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI WILAYAH KPP PRATAMA PANDEGLANG - Rudiyanto Rudiyanto; Hidayatullah Hidayatullah (The Asia Pacific Journal Of Management Studies, 2016)
The number of tax payers is increase for years . But, it is not balanced with the level of tax compliance. The compliance problem becomes an obstacle in optimizing the tax revenue. This study examines the level of compliance of individual taxpayers  in Pandeglang by using several independent variables s uch as awareness of the tax payer and the service tax authorities. The purpose of this study was to analyze the influence  of  awareness  of  the  taxpayer  and  the  service  tax  authorities  against  an individual taxpayer compliance.  The population of this study is individual taxpayers. Based on data from the KPP  Pratama  Pandeglang,  until  the  end  of  2015  there  were  89.193  individual taxpayers.  Not  all  population  have  been  used  in  this  study  to  the  time  and  cost  efficiency. Therefore, carried out the sampling. Sampl ing was  done by simple random sampling  method.  The  number  of  sample  is  100  people.  Primary  data  collection method  used  is  a  survey  method  using  questionnaires  media.  Data  analysis techniques used in this study is the technique of multiple regression analys is.  Based on the results of the analysis undertaken concluded that awareness of the tax payer and the service tax authorities have a positive and significant impact on taxpayer compliance.